Sense and singularity : Jean-Luc Nancy and the interruption of philosophy - Van den Abbeele, Georges (Fordham University Press, 2023)
"Philosophical thinking is interrupted by the finitude of what cannot be named, on the one hand, and that within which it is subsumed as one of multiple modes of sense-making, on the other. Sense and Singularity elaborates Jean-Luc Nancy's philosophical project as an inquiry into the limits or finitude of philosophy itself, where it is interrupted, and as a practice of critical intervention where philosophy serves to interrupt otherwise unquestioned ways of thinking. Nancy's interruption of philosophy, Van Den Abbeele argues, reveals the limits of what philosophy is and what it can do, its apocalyptic end and its endless renewal, its Sisyphean interruption between the bounds of infinitely replicating sense and the conceptual vanishing point that is singularity"-- Provided by publisher.
Keywords: Nancy, Jean-Luc; Finite, The.; Sense (Philosophy); Fini.; Sensibilité (Philosophie); PHILOSOPHY / Movements / Deconstruction.; Finite, The; Electronic books.